Unravelling the link between chronic inflammation and primary hyperparathyroidism: a systematic review - Gheorghe-Milea, Ana; Stănoiu-Pînzariu, Oana; Georgescu, Carmen Emanuela (Frontiers in Immunology, 2025)
IntroductionPrimary hyperparathyroidism (PHPT) is a multisystemic endocrine disorder characterized by an incompletely understood pathogenesis, a complex clinical picture and various complications. Chronic inflammation represents a state that can affect the normal function of cells and cause tissue damage, therefore increasing the risk of certain diseases, including cancer, metabolic, cardiovascular or neurodegenerative disorders.AimReviewing existing data on markers of inflammation in patients with PHPT, with potential implications in understanding the pathogenesis of PHPT, stratifying the risk for complications and providing new diagnostic biomarkers and a personalized therapeutic approach, especially in patients who cannot be operated on.MethodsA systematic review was conducted by searching in four electronic databases (PubMed, Embase, Web of Science and Scopus) and summarizing data from studies that evaluated inflammatory markers in patients with PHPT.ResultsThe review included a total of 28 articles, encompassing data from 1572 patients diagnosed with PHPT. Various markers associated with chronic inflammation, including High sensitivity C-Reactive Protein (CRP), Tumor Necrosis Factor-α, Interleukin (IL)-6, and fibrinogen, were found to be elevated in PHPT patients. White blood count (WBC) values were similar in patients and controls in most studies, while for some markers derived from the full blood count significant differences were found between these groups. Correlations between PTH levels and several biomarkers, including IL-6, CRP and WBC, were also identified. Data on the impact of parathyroidectomy on inflammation parameters were conflicting.ConclusionThe findings from this systematic review suggest an association between chronic inflammation and primary hyperparathyroidism, underscoring the potential role of inflammation as a mediator of PHPT-related complications. Targeting inflammatory pathways may offer novel therapeutic strategies for mitigating systemic effects of PHPT and improving patient outcomes.